Self‐Assembly of a Supramolecular, Three‐Dimensional, Spoked, Bicycle‐like Wheel1. Issue 30 (13th June 2013) - Lu, Xiaocun; Li, Xiaopeng; Cao, Yan; Schultz, Anthony; Wang, Jin‐Liang; Moorefield, Charles N.; Wesdemiotis, Chrys; Cheng, Stephen Z. D.; Newkome, George R.
<x xml:space="preserve">Abstract</x> Where there′s a wheel, there′s a way: The terpyridine‐based title system has been synthesized through a facile self‐assembly process. Two tris(terpyridine) ligands possessing angles of either 120° or 60° between adjacent tpy units were mixed with a stoichiometric amount of Zn2+ (2:6:12) to generate the desired coordination‐driven bicycle‐like wheel (90 % yield).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>